ANALISIS KONSEP INTERAKSI MANUSIA DAN KOMPUTER PADA ANTARMUKA SISTEM INFORMASI AKADEMIK UNIVERSITAS MUHAMMADIYAH PONOROGO - Desriyanti . (MULTITEK INDONESIA, 2017)
Academic Information System Students is an existing system, where student academic activities will be recorded in the system from the first semester until the last semester. This study aims to obtain a description of the quality of the interface, knowing the criteria  to the user in accordance with the various dialogues and concepts of human and computer interaction on the interface of a student academic information system. The methods used are observation, documentation, and the questionnaire which is analyzed SPSS. In order to have a deep discussion, variable groupings are done through the validation test table variable r product moment person with df (degree of freedom). For the results of the scores for each respondent can be seen in the table results of the calculation of all respondents. Thus, test One Sample t test If Sig 0.05 then Ho accepted If Sig 0.05 then Ho is rejected. From the test One Sample t test shows Sig = 0.000, then Sig 0.05 which means Ho rejected. So, from the One Sample T test, it is indicated that “the application of the concept of human and computer interaction on the interface in the academic information has done well.